2012
DOI: 10.1103/physrevd.85.102005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino processes with power law dispersion relations

Abstract: We compute various processes involving neutrinos in the initial and/or final state and we assume that neutrinos have energy momentum relation with a general power law E 2 = p 2 + ξ n p n correction due to Lorentz invariance violation. We find that for n > 2 the bounds on ξ n from direct time of flight measurement are much more stringent than from constraining the neutrino Cerenkov decay process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…(2.12)) is suppressed but the |M | 2 is enhanced. The net effect however is a suppression in the Γ(π − → µ −ν µ ) for this case also [11], as shown in figure 1 for…”
Section: Jhep11(2015)022mentioning
confidence: 83%
See 1 more Smart Citation
“…(2.12)) is suppressed but the |M | 2 is enhanced. The net effect however is a suppression in the Γ(π − → µ −ν µ ) for this case also [11], as shown in figure 1 for…”
Section: Jhep11(2015)022mentioning
confidence: 83%
“…Depending on the sign of ξ n , the neutrinos (antineutrinos) can be either superluminal (ξ n < 0) or subluminal (ξ n > 0). For the superluminal case, it has been shown [11,12] that the presence of the extra terms in the dispersion results in a suppression of π and K decay widths. The phase space suppression for both the subluminal and superluminal dispersions for meson decay and the Cerenkov process ν → νe + e − has been noticed in [9,[13][14][15][16] with limits on Lorentz violation parameters from IceCube events.…”
Section: Jhep11(2015)022mentioning
confidence: 99%
“…Threshold effects A key feature of threshold processes is to introduce some small change to the neutrino dispersion relation based on an LV scenario [91]. These changes can produce effects [137][138][139][140][141][142][143][144][145][146] that become more significant at higher energies. The dispersion relation modifications in the SME are tied to the appropriate coefficients as in, for instance [148,149].…”
Section: Coefficientmentioning
confidence: 99%
“…At high energy, as a result of modified dispersion relation, photon becomes massive enough to suppress the π 0 decay into two photons. The possible Lorentz invariance violation is motivated from quantum gravity [16][17][18] and in many studies [19][20][21][22][23][24][25] it has been shown that LIV becomes important at very high energy scale. There are stringent constraints on LIV in photon [13][14][15]26] and fermion [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%